If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 6 = 4 Reorder the terms: 6 + 5n = 4 Solving 6 + 5n = 4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5n = 4 + -6 Combine like terms: 6 + -6 = 0 0 + 5n = 4 + -6 5n = 4 + -6 Combine like terms: 4 + -6 = -2 5n = -2 Divide each side by '5'. n = -0.4 Simplifying n = -0.4
| Xt-5=k | | 9+5=5a+5 | | 19x-41=41 | | 7x+18y=4 | | 19x-41=-41 | | 7y-9=8y-1 | | -2(r+6)=-37 | | 2-2n=n+64 | | 0.33=6 | | 2x^2-10x=6 | | 10x-3=-17 | | (3k-7)/(5)=16 | | 49+1-4c=39c-2 | | 2k+k+4= | | [t+5]+3=12 | | 7-2x=0 | | 6x+8=4x+50 | | 3x+8=8+2x+x | | 729=x^3 | | 4(d-20)=1 | | 245=-7a | | (36-5x)+(36-5x)+4x+4x=x | | 3x+28=7(x+4)-4x | | 2(6+3)=18-3(16-3d) | | 6+12=16 | | x+17=36-x | | x=20-0.5y | | 5=1-2n+5 | | 4(d-5)=1 | | 5m-14=8m+4 | | 2.5x-(-8.2)=26.7 | | -8n+4(1+5)=6n-14 |